Identifying the Needs of Visual Sensory Disabilities in Developing Interests and Talents at PPSDSN - Cahyaningsih, Riyan Dwi; Fakhruddin, Fakhruddin; Widiyanto, Widiyanto; Yuwono, Agus (Universitas Negeri Semarang, 2024)
Visual sensory disabilities have the desire to be accepted in society and obtain equal rights in the process of developing their interests and talents. The aim of this research is first, to find out the identification of needs for visual sensory disabilities in the process of developing themselves at PPSDSN (Social Service Home for Visual Sensory Disabilities) Pendowo, Kudus district. Second, find out the process of developing interests and talents for visual sensory disabilities at PPSDSN (Social Service Home for Visual Sensory Disabilities) Pendowo, Kudus district. The method used in this research uses qualitative methods. This research data uses observation, interview and documentation techniques. Data collection techniques in this research used observation, interview and documentation techniques. Data analysis uses reduction techniques, data presentation, and drawing conclusions. The results of this research are first, the needs of the beneficiaries regarding self-development at the PPSDSN (Social Service Home for the Visually Sensory Disabled) Pendowo, Kudus Regency, are influenced by Human Resources and programs implemented at the PPSDSN (Social Service Home for the Visually Sensory Disabled) Pendowo, Kudus Regency. Second, the process of developing interests and talents is adjusted to the program chosen by the beneficiary and their willingness to develop themselves according to the program being implemented.